Differences In Patterns of Fiber Consumption and Physical Activity In Students With and Without Functional Constipation at Health Polytechnic, Tasikmalaya, Cirebon Area - Adijaya, Yoga; Subardjo, Yovita Puri; Prasetyo, Teguh Jati (Journal of Global Nutrition, 2024)
Infrequent fiber consumption patterns and light physical activity can cause functional constipation. The purpose of this study was to analyze differences in fiber consumption patterns and physical activity in students with and without functional constipation at the Tasikmalaya Health Polytechnic, Cirebon Region. This study uses a cross-sectional, using a stratified random sampling technique involving 100 students. Data collection using Rome III questionnaire, Food Frequency Questionnaire, and International Physical Activity Questionnaire. Bivariate analysis using Chi-Square test and Fisher's Exact test. The results showed that students with frequent fiber consumption patterns were 39% and rarely 61%, with Chi-square (p = 0.384). While students with light physical activity were 89%, and 11% heavy, with the results of the Fisher's Exact (p = 0.053). It can be concluded that this study shows that there is no significant difference between fiber consumption patterns and physical activity in students with and without functional constipation.